2002
DOI: 10.1038/sj.bjc.6600351
|View full text |Cite
|
Sign up to set email alerts
|

Decreased proliferation of human melanoma cell lines caused by antisense RNA against translation factor eIF-4A1

Abstract: Control of translation initiation was recognised as a critical checkpoint for cell proliferation and tumorigenesis. In human melanoma cells, we have previously reported consistent overexpression of translation initiation factor eIF-4A1. Here, we investigated by transfection of antisense constructs its significance for the control of melanoma cell growth. The tetracyclineinducible expression system was established in melanoma cells, and three fragments of the 5'-, central-, and 3'-portion of the eIF-4A1 cDNA we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…There is much data indicating that a high level of cell division, measured by rapid incorporation of labeled DNA precursors (33) or the activation of cell cycle proteins (34), is correlated within a particular tumor type with a poor survival. In addition, studies of the expression of genes involved in protein synthesis suggest that a high level of protein synthesis is also associated with poor prognosis (35,36). However, it is also true that some studies in tumors for which effective chemotherapy is available have shown that the reverse is true, that cancers undergoing more rapid cell division have a greater potential for long-term survival after treatment.…”
Section: Discussionmentioning
confidence: 96%
“…There is much data indicating that a high level of cell division, measured by rapid incorporation of labeled DNA precursors (33) or the activation of cell cycle proteins (34), is correlated within a particular tumor type with a poor survival. In addition, studies of the expression of genes involved in protein synthesis suggest that a high level of protein synthesis is also associated with poor prognosis (35,36). However, it is also true that some studies in tumors for which effective chemotherapy is available have shown that the reverse is true, that cancers undergoing more rapid cell division have a greater potential for long-term survival after treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Translational regulation and control of ribosome biogenesis are vital cellular processes that directly impact on cell proliferation and growth. Activated RAS and AKT controls protein translation (29,30) and the combination of activated RAS and AKT has been shown to recruit specific growth-promoting mRNAs to polysomes in glial cells (31). Because we found that several proteins associated with protein translation were aberrantly expressed in Nf1À/À astrocytes, we sought to determine whether these protein expression changes were associated with an increase in the overall rate of protein synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…However, the functional role of eIF4G phosphorylation has not been reported yet. Elevated levels of the eIF4A helicase are detected in human melanoma and hepatoma cells (Eberle et al, 1997(Eberle et al, , 2002Shuda et al, 2000). Furthermore, a novel putative tumor suppressor, Pdcd4, has been characterized as an inhibitor of eIF4A activity and cap-dependent translation (Yang et al, 2003).…”
Section: Translation Initiation Factors Are Regulated By Aktmentioning
confidence: 99%